2021
DOI: 10.1155/2021/9200267
|View full text |Cite
|
Sign up to set email alerts
|

Mean Deviation Coupling Control for Multimotor System via Global Fast Terminal Sliding Mode Control

Abstract: In view of the shortcomings of the existing multimotor synchronous control strategy, a new method of mean deviation coupling control for multimotor system via global fast terminal sliding mode control is proposed. Firstly, the mathematical model of permanent magnet synchronous motor (PMSM) under a d - q reference frame is established. Next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In 1995, Diakoulaki proposed the CRITIC (Criteria Importance Though Intercrieria Correlation) method to determine the objective weights through the intensity of comparison and conflict between the corresponding data of indicators [15]. Open Journal of Applied Sciences However, some scholars suggested that mean deviation has a better deconstructive function than standard deviation [16], which more accurately reflects the average degree of variation among indicators. Additionally, in cases where the absolute values of the corresponding figures of each indicator are identical, the correlation between the indicators will be the same [17].…”
Section: Determination Of Index Weights Based On Improved Criticmentioning
confidence: 99%
“…In 1995, Diakoulaki proposed the CRITIC (Criteria Importance Though Intercrieria Correlation) method to determine the objective weights through the intensity of comparison and conflict between the corresponding data of indicators [15]. Open Journal of Applied Sciences However, some scholars suggested that mean deviation has a better deconstructive function than standard deviation [16], which more accurately reflects the average degree of variation among indicators. Additionally, in cases where the absolute values of the corresponding figures of each indicator are identical, the correlation between the indicators will be the same [17].…”
Section: Determination Of Index Weights Based On Improved Criticmentioning
confidence: 99%
“…The modeling of PMSM can be found in the literature. 9 The population size and limit affect the performance of the ABC algorithm. First, a test was done to find the appropriate population size, and results are shown in Table 2.…”
Section: Simulation Analysis and Validationmentioning
confidence: 99%
“…To further promote the reliability and effectiveness of RCC, Shi et al 8 presented an improved relative coupling control structure (IRCC) that introduced an additional speed controller to treat all the motors as an entity. Zhu et al 9 proposed a mean relative coupling control (MRCC) for multi-motor systems. In MRCC, the average speed was used to replace the speed difference between each motor, which simplified the structure of the RCC structure and reduced the calculation of the system.…”
Section: Introductionmentioning
confidence: 99%
“…When the derivative time is too long, fluctuations occur in this mode and the closed loop becomes unstable. Then, in real-world applications, the PID parameters should be carefully tuned [5][6][7].…”
Section: Introductionmentioning
confidence: 99%